Spatiotemporal responses of a desert dwelling ungulate to increasing aridity in North-eastern Namibia. (August 2020) - Lehmann, D.; Mfune, J.K.E.; Gewers, E.; Cloete, J.; Aschenborn, O.H.-K.; Mbomboro, L.; Kasaona, S.; Brain, C.; Voigt, C.C.
Abstract: Ungulates are famous for large-scale movements in response to local and regional changes in plant productivity. However, it is poorly understood how non-migratory ungulates respond towards shortages in plant availability. In the arid Kunene Region of Namibia, we studied the variation of home ranges and habitat use of gemsbok during a period of severe drought that led to a critical food shortage. We then related the spatiotemporal behaviour of gemsbok to relative plant greenness and local plant productivity, using local Normalized Differenced Vegetation Indices (NDVI) as a proxy, and to satellite images to assess habitat types and topography. Core home range sizes of gemsbok did not vary with decreasing local NDVI values, while total home-ranges increased with decreasing NDVI values. Gemsbok responded to resource fluctuations by using a combination of habitats differing in plant productivity, topography and vegetation cover. Gemsbok increased the number of habitats used when NDVI values decreased. Individuals remained non-migratory even during the period of peak drought. Non-migratory gemsboks are capable of exploiting local resources efficiently by adjusting their habitat use, when facing declining resources and unpredictable food shortages. Our study provides important information on the habitat use of gemsbok for the sustainable management of populations in arid environments. Highlights: Desert-dwelling gemsbok selected their resource habitats as aridity and associated environmental uncertainties increased. Gemsbok use a combination of different interlacing habitats allowing them to survive in even extreme desert environments. Higher NDVI values did not fully explain the movement behaviour and habitat selection of Gemsbok. Inter-individual variation in home range and habitat use reflect dietary preferences of gemsbok. Conserving corridors between core refuge habitats may support the sustainable management of ungulate populations.